Strengthening Character Education Through Behaviorist Approaches: Strategic Management in Shaping Students’ Ethics and Morality - Bahri, Saiful; Fauzi, Ahmad; Zaini, Bahruddin (Journal of Educational Management Research, 2025)
This study examines the strategic role of madrasah ibtidaiyah in strengthening character education to shape students’ ethics and morals from an early age, particularly amid growing concerns over moral degradation among the younger generation. Adopting a qualitative case study approach, data were collected through participatory observation, in-depth interviews with teachers, principals, and students, as well as analysis of learning documents and school programs. The research focuses on the application of a behavioristic approach, emphasizing habituation and reinforcement in shaping student behavior. Findings reveal that character values—such as discipline, responsibility, politeness, and honesty—are integrated into both classroom instruction and daily school routines, including greetings, congregational prayers, and community service. Positive reinforcement through rewards and corrective measures via punishment are applied consistently to encourage desired behaviors. Continuous repetition, modeling, and reinforcement are found to be effective in embedding these values, creating a systematic and well-directed framework for moral and ethical development. The study concludes that a behavioristic approach, when implemented strategically within a religious-based elementary education setting, offers a practical and impactful method for fostering students’ character, ensuring alignment between moral values and daily conduct.